1992
DOI: 10.1002/ijc.2910500428
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by vaso‐active intestinal peptide of gastric carcinogenesis induced by N‐methyl‐N'‐nitro‐N‐nitrosoguanidine in rats

Abstract: The effects of vaso-active intestinal peptide (VIP) on gastric carcinogenesis induced by N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) were investigated in Wistar rats given VIP every other day for 27 weeks after oral administration of MNNG for 25 weeks. In week 52, administration of VIP caused a significant increase in the incidence of gastric cancers, but did not influence their histological appearance. VIP significantly increased the labeling indices of the antral mucosa. Our findings indicate that VIP enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Similarily, we previously reported that prolonged administration of tyrosine methyl ester, neurotensin and vasoactive intestinal peptide significantly increased the labelling index of the antral cells, but they had little or no influence on the labelling index of the fundic epithelial cells (Tatsuta et al, 1989d(Tatsuta et al, , 1991Iishi et al, 1992). However, the reason why the fundus and antrum differ is not known.…”
Section: Discussionsupporting
confidence: 67%
“…Similarily, we previously reported that prolonged administration of tyrosine methyl ester, neurotensin and vasoactive intestinal peptide significantly increased the labelling index of the antral cells, but they had little or no influence on the labelling index of the fundic epithelial cells (Tatsuta et al, 1989d(Tatsuta et al, , 1991Iishi et al, 1992). However, the reason why the fundus and antrum differ is not known.…”
Section: Discussionsupporting
confidence: 67%
“…It is not clear if the autocrine regulation of VIP in gastric cancer cells exists and if so, how it affects gastric cancer cells. Kim reported the VIP inhibited the growth of AGS gastric cancer cells by inhibiting c‐myc expression in vitro , 17 but Iishi reported that VIP enhanced the development of rat gastric cancer induced by MNNG in vivo, 18 so we speculated that gastric cancer cells might exist in the autocrine regulation of VIP.…”
Section: Discussionmentioning
confidence: 89%
“…The physiological functions of VIP in the GI tract are associated with the secretion and motor of the digestive system. Recently, many studies showed that VIP was closely correlated with malignancy, 6–18 and some studies showed that VIP also had close correlation with gastric cancer, but some controversies and questions still exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation